Telomerase subunit Est2 marks internal sites that are prone to accumulate DNA damage - Pandey, Satyaprakash; Hajikazemi, Mona; Zacheja, Theresa; Schalbetter, Stephanie; Neale, Matthew J.; Baxter, Jonathan; Guryev, Victor; Hofmann, Andreas; Heermann, Dieter W.; Juranek, Stefan A.; Paeschke, Katrin (BMC biology, 2021)
The main function of telomerase is at the telomeres but under adverse conditions telomerase can bind to internal regions causing deleterious effects as observed in cancer cells.